The Epidemic as Stigma: The Bioethics of Opioids. Issue 4 (December 2017) - Buchman, Daniel Z.; Leece, Pamela; Orkin, Aaron
In this paper, we claim that we can only seek to eradicate the stigma associated with the contemporary opioid overdose epidemic when we understand how opioid stigma and the epidemic have co-evolved. Rather than conceptualizing stigma as a parallel social process alongside the epidemiologically and physiologically defined harms of the epidemic, we argue that the stigmatized history of opioids and their use defines the epidemic. We conclude by offering recommendations for disrupting the burden of opioid stigma.